2010
DOI: 10.1093/jopart/muq061
|View full text |Cite
|
Sign up to set email alerts
|

Networks in Public Administration Scholarship: Understanding Where We Are and Where We Need to Go

Abstract: This article examines the road that network scholarship has followed in Public Administration. We look at the historical drivers of the use of networks in practice and scholarship in the field and discuss how that has shaped the current literature. The body of the article focuses on the current challenges that network scholars face in the discipline, specifically basic theoretical issues, knowledge about formal networks, knowledge about informal networks, and methodological issues. We close the article with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
356
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(378 citation statements)
references
References 60 publications
5
356
0
4
Order By: Relevance
“…Seeds for the study were identified based on consultations with domain experts as well as recent reviews, including Berry et al (2004) and Isett et al (2011). Because snowball samples move forward in time, the seeds chosen are between 10 and 15 years old (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds for the study were identified based on consultations with domain experts as well as recent reviews, including Berry et al (2004) and Isett et al (2011). Because snowball samples move forward in time, the seeds chosen are between 10 and 15 years old (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…In order to address this lack of coherence, scholars have regularly made efforts to organize this literature either by offering analytical frameworks (Agranoff and McGuire, 1998;Klijn, 1996; or by extensive literature reviews (Berry et al, 2004;Isett et al, 2011;Provan et al, 2007;Robinson, 2006). We go beyond the previous research by examining a representative set of articles in public administration to refine a research taxonomy that sorts publications into coherent clusters based upon the outcomes explained in the studies.…”
Section: Network Research Lacks Coherencementioning
confidence: 99%
“…Facing this situation, networks tend to adopt more formal modes of governance, as Lead Organization or NAO (Provan & Kenis, 2008). Isett, Mergel, Leroux, Mischen and Rethemeyer (2011) reinforce Provan and Kenis' (2008) perspective, mentioning that networks begin with an informal common structure and tend to become more formal over time.…”
Section: Dependencymentioning
confidence: 99%
“…The problem solving takes place in complex games and networks where each actor behaves strategically, guided by diverging or conflicting perceptions and rules (Koppenjan & Klijn, 2004) & (Isett, et al, 2011). To illustrate, the government, public and private organisations are challenged with these long-dated controversies over complex socio-problems.…”
Section: Policy Network: Evolution and Conceptsmentioning
confidence: 99%
“…Hence networks are embedded in a specific policy context, and the behaviour of network actors is defined by that particular context' (Isett, et al, 2011). Perhaps formal networks arise from diverse institutional forms that subsist on diverse funding stream that carry differing regulations and rules for implementation.…”
Section: Networked Politics In Afghanistanmentioning
confidence: 99%